A Suggested Program for Developing EFL Depth and Breadth Vocabulary Learning among Official Language Preparatory School Pupils - Mohammed, Fatma Sadek; Emam, Rehab Ahmed Hamdy Hussien; Abdel-Haq, Eman Mohammed; Zaza, Mona Salem Mahmoud (جامعة بنها - كلية التربية, 2019)
integration between incidental and intentional learning to develop second year official language preparatory school pupils’ EFL depth and breadth vocabulary learning. The participants of the study were (60) second year preparatory stage pupils from Ahmed Zweil Official Language School - Benha - Alqalubia. They were assigned into two groups; the experimental group (N = 30) and the control group (N = 30). The instruments used included a topic selection questionnaire, EFL vocabulary tests (two equivalent forms: one for pre-test and the other one for post-test). A program based on integrating incidental and intentional learning was prepared to show how to apply the integration between incidental and intentional learning. The instruments were administrated before and after the experiment. T- test was used to compare the mean scores of (he control group and experimental one in the pre-post applications. Findings of the study showed that the experimental group outperformed the control group in EFL vocabulary depth and breadth learning. Consequently, the program based on the integration between incidental and intentional learning was effective in developing EFL depth and breadth vocabulary learning.
Keywords: التعليم المتوسط -- تدريس اللغة الإنجليزية -- اللغة الإنجليزية كلغة أجنبية